Transformation of Religious Feelings of Vulnerable Populations Under Conditions of Large-Scale Dangers in the Chernivtsi Region - Lazorevych, Iryna (Occasional papers on religion in Eastern Europe, 2022)
Solving the challenges facing humanity requires the combined efforts of all humanity using a comprehensive approach. This also applies to the problem of HIV. In particular, in the context of the war in Ukraine, the crisis of marginalized groups deepened and people with HIV began to face more challenges than usual (because their treatment, which requires constant supervision and medication, is at risk). This article analyzes a survey conducted at the beginning of the invasion about the level of religiosity and trust in the church among HIV-positive people in wartime conditions. The issue of the problems of marginalized groups and the role of the church in solving them, the influence of stereotypes and prejudices on the formation of internal self-stigmatization, and the existence of an educational gap in the context of health care as a basis for fear of others is updated.